Chronic disease mortality associated with infectious agents: A comparative cohort study of migrants from the Former Soviet Union in Israel and Germany - Winkler Volker; Paltiel Ari M; Ott Jördis J; Becher Heiko (BMC, 2008)
Abstract Background Prevalence of infectious diseases in migrant populations has been addressed in numerous studies. However, information is sparse on their mortality due to chronic diseases that are aetiologically associated with an infectious agent. This study investigates mortality related to infectious diseases with a specific focus on cancers of possibly infectious origin in voluntary migrants from the Former Soviet Union residing in Israel and in Germany. Methods Both groups of migrants arrived from the Former Soviet Union in their destination countries between 1990 and 2001. Population-based data on migrants in Israel were obtained from the Israel Central Bureau of Statistics. Data for migrants in Germany were obtained from a representative sample of all migrants from the Former Soviet Union in Germany. Cause of death information was available until 2003 for the Israeli cohort and until 2005 for the German cohort. Standardized mortality ratios were calculated relative to the destination country for selected causes of death for which infectious agents may be causally involved. Multivariate Poisson regression was applied to assess differences in mortality by length of residence in the host country. Results Both in Israel and in Germany these migrants have lower overall mortality than the population in their destination countries. However, they have significantly elevated mortality from viral hepatitis and from stomach and liver cancer when compared to the destination populations. Regression analysis shows that in Israel stomach cancer mortality is significantly higher among migrants at shorter durations of residence when compared to durations of more than nine years. Conclusion Higher mortality from cancers associated with infection and from viral hepatitis among migrants from the Former Soviet Union might result from higher prevalence of infections which were acquired in earlier years of life. The results highlight new challenges posed by diseases of infectious origin in migrants and call attention to the link between communicable and non-communicable diseases.